Water works - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Smallholder irrigation technology: Prospects for sub-Saharan Africa By M Kay, FAO & International Programme for Technology and Research in Irrigation and Drainage, Rome 2001. 42 pp. ISBN 92 5 104 594 1 US$12 Euro 13.40